2020
DOI: 10.1055/s-0040-1721372
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination of Low Birth Weight Infants in Washington State

Abstract: Objective The U.S. Advisory Committee on Immunization Practices (ACIP) recommends that infants born weighing less than 2,000 g receive the hepatitis B (HepB) vaccine at hospital discharge or 30 days of age. This study aimed to assess timely HepB vaccination among low birth weight infants. We hypothesized that many of these vulnerable infants would fail to receive their HepB birth dose on time. Study Design This retrospective cohort study included Washington State infants born weighing less than 2,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…On the one hand, the birth dose of HepB among them showed considerable delay. [23][24][25] The present study also found that only 45.9% of preterm infants received their birth dose of HepB on time, compared to 93.5% in the full-term group. On the other hand, preterm infants may not be able to elicit a strong immune response after HepB vaccination due to their underdeveloped immune function, which is characterized by fewer absolute numbers of lymphocytes, T cells, B cells and T-helper cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…On the one hand, the birth dose of HepB among them showed considerable delay. [23][24][25] The present study also found that only 45.9% of preterm infants received their birth dose of HepB on time, compared to 93.5% in the full-term group. On the other hand, preterm infants may not be able to elicit a strong immune response after HepB vaccination due to their underdeveloped immune function, which is characterized by fewer absolute numbers of lymphocytes, T cells, B cells and T-helper cells.…”
Section: Discussionsupporting
confidence: 70%
“…Preterm infants are a unique population for whom HepB vaccination and the long‐term persistence of its immune response are also matters of great concern. On the one hand, the birth dose of HepB among them showed considerable delay 23–25 . The present study also found that only 45.9% of preterm infants received their birth dose of HepB on time, compared to 93.5% in the full‐term group.…”
Section: Discussionsupporting
confidence: 62%